Welding : theory and practice - Olson, David L (David LeRoy); Dixon, Ray; Liby, Alan L. (Materials processing, theory and practices, 1990)
This volume gives a comprehensive and thorough review on recent advances in the science of welding and provides a treatise for their application in day-to-day welding activities. The essential science of welding is presented for the first time in a style that is comprehensible to the craftsman, engineer and scientist. The application of welding technology requires familiarity with a broad spectrum of engineering and science. The practitioners of this technology need to be familiar with mathematics, physics, chemistry, metallurgy, electrical engineering, and mechanical engineering to mention the basics. These practitioners may only have a scant knowledge in all areas, and this book is intended to provide those practising welding with a broad but subtly in-depth overview of the subject. To accomplish this the book is divided into: weld pool chemistry and microstructure, processes: high energy density; low energy density; and bonding, heat input and associated stress, and computer control. Each of these areas addresses the literature, the fundamental science and engineering, and where the technology stands with respect to the topic. The knowledge level anticipated is not that of a senior engineer or researcher, although they could enjoy the works as much as anyone, but is more designed for those involved in the daily practise of welding. Thus the book will be of interest to craftsmen, students, engineers, researchers, managers, and those interested in the Theory and Practice of welding.